2002
DOI: 10.1128/mcb.22.11.3674-3684.2002
|View full text |Cite
|
Sign up to set email alerts
|

B56-Associated Protein Phosphatase 2A Is Required For Survival and Protects from Apoptosis in Drosophila melanogaster

Abstract: Protein phosphorylation and specific protein kinases can initiate signal transduction pathways leading to programmed cell death. The specific protein phosphatases regulating apoptosis have been more elusive. Using double-stranded RNA-mediated interference (RNAi), the role of protein phosphatase 2A (PP2A) in cellular signaling was investigated. Knockdown of A or C subunits individually or of combined B subunits led to concurrent loss of nontargeted PP2A subunits, suggesting that PP2A is an obligate heterotrimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
108
5

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 50 publications
22
108
5
Order By: Relevance
“…The same study also confirmed earlier reports demonstrating that, in yeast, subunit stability is not linked to heterotrimer formation [20][21][22][23][24]. However, in Drosophila melanogaster Schneider cells, the absence of all B-type subunits promotes the degradation of the A and C subunits, and vice versa [25,26], which indicates that PP2A enzymes are obligate trimers in this system. In mammalian cells, catalytic-, PR55/B-and PR61/B 0 subunits are only stable when bound to the A subunit, whereas free [32].…”
Section: Pp2a a Structural Centipede With Multiple Functionssupporting
confidence: 90%
“…The same study also confirmed earlier reports demonstrating that, in yeast, subunit stability is not linked to heterotrimer formation [20][21][22][23][24]. However, in Drosophila melanogaster Schneider cells, the absence of all B-type subunits promotes the degradation of the A and C subunits, and vice versa [25,26], which indicates that PP2A enzymes are obligate trimers in this system. In mammalian cells, catalytic-, PR55/B-and PR61/B 0 subunits are only stable when bound to the A subunit, whereas free [32].…”
Section: Pp2a a Structural Centipede With Multiple Functionssupporting
confidence: 90%
“…4B, inset). As reported previously [30,31] knockdown of the PP2A catalytic subunit also caused a loss of the B56-1 subunit due to instability of the free protein. Depletion of the B56-1 protein had no detectable effect on the basal level of dS6K or the dephosphorylation caused by amino acid starvation (Fig.…”
Section: Effects Of Depleting Pp2a Regulatory Subunits On Ds6k Phosphsupporting
confidence: 76%
“…Previous studies showed that the two Drosophila B56 subunits cooperate to promote cell survival [30][31][32]. B56-1 and -2 could also cooperate to regulate the phosphorylation of dS6K.…”
Section: Effects Of Depleting Pp2a Regulatory Subunits On Ds6k Phosphmentioning
confidence: 99%
See 2 more Smart Citations